COMPARISON OF GROW-OUT METHODS OF SAND LOBSTER (Panulirus homarus) WITH RECIRCULATION AQUACULTURE SYSTEM (RAS) AND FLOW-THROUGH (FT): STUDY OF BIOLOGICAL ACTIVITIES - Bambang Widyo Prastowo; Manja Meyky Bond; Betutu Senggagau (University of Lampung, 2021)
Aquaculture technology using Recirculating Aquaculture System (RAS) is basically a technology for fish farming by reusing water used in production. This technology is based on the use of mechanical and biological filters, and this method in principle can be used for all species cultivated in aquaculture such as fish, shrimp, shellfish and others. This study was carried out at Station for Investigation of Fish Health and Environment (LP2IL) Serang’s field test facility starting from June to November 2020 (110 days of sand lobster grow-out period). In this study, the RAS system used for grow-out of sand lobster uses a series of containers, compartments, tanks and equipment for water treatment with the following purification stages (1) sedimentation containers; (2) physical filtration; (3) biological filtration, (4) disinfection of water by UV irradiation, (5) removal of CO2, (6) clean water reservoirs and (7) tanks for grow-out of sand lobster. In this study, a series of tests were carried out on several biological activities parameters of sand lobster including growth weight and length, FCR, SR, molting and biomass, which were measured every two weeks during grow-out period. From the results of this study activity, it is found that the biological parameters of sand lobster grow-out with RAS is improving when compared to sand lobster grow-out in flow through water system (FT).